The Mechanism of High-Output Cardiac Hypertrophy Arising From Potassium Channel Gain-of-Function in Cantú Syndrome. Issue 1 (18th June 2020) - McClenaghan, Conor; Huang, Yan; Matkovich, Scot J; Kovacs, Attila; Weinheimer, Carla J; Perez, Ron; Broekelmann, Thomas J; Harter, Theresa M; Lee, Jin-Moo; Remedi, Maria S; Nichols, Colin G
Abstract: Dramatic cardiomegaly arising from gain-of-function (GoF) mutations in the ATP-sensitive potassium (KATP ) channels genes, ABCC9 and KCNJ8, is a characteristic feature of Cantú syndrome (CS). How potassium channel over-activity results in cardiac hypertrophy, as well as the long-term consequences of cardiovascular remodeling in CS, is unknown. Using genome-edited mouse models of CS, we therefore sought to dissect the pathophysiological mechanisms linking KATP channel GoF to cardiac remodeling. We demonstrate that chronic reduction of systemic vascular resistance in CS is accompanied by elevated renin–angiotensin signaling, which drives cardiac enlargement and blood volume expansion. Cardiac enlargement in CS results in elevation of basal cardiac output, which is preserved in aging. However, the cardiac remodeling includes altered gene expression patterns that are associated with pathological hypertrophy and are accompanied by decreased exercise tolerance, suggestive of reduced cardiac reserve. Our results identify a high-output cardiac hypertrophy phenotype in CS which is etiologically and mechanistically distinct from other myocardial hypertrophies, and which exhibits key features of high-output heart failure (HOHF). We propose that CS is a genetically-defined HOHF disorder and that decreased vascular smooth muscle excitability is a novel mechanism for HOHF pathogenesis.